Bioaccumulation of Selected Metals and Non-Metals in Mycelium and Fruit Bodies of Ectomycorrhizal Fungi - Vinichuk, M. M.; Skyba, G. V.; Yelnikova, T. O.; Mandro, Y. N. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2019)
Purpose. We attempted to quantify the contribution of wild-growing mycelium of ectomycorrhizal fungi to the soil level of selected metals and non-metals in upper (0−10 cm) layer of forest soil of  boreal forest ecosystems. The content of selected elements were also analyzed and compared in such fractions of soil as bulk soil, rhizosphere and soil-root interface. Specifically we analyzed the content of phosphorus (P), manganese (Mn), iodine (I), chromium (Cr), nickel (Ni), copper (Cu), zinc (Zn), cadmium (Cd), cobalt (Co), mercury (Hg) lead (Pb) and arsenic (As). Methods. The concentration of the elements in the samples (dry weight, d.w.) was determined by the mass spectrometric method (ICP-MS) in the laboratory ALS Scandinavia AB, Luleå according to the method given in Rodushkin et al. [13]. Statistical data processing was performed using dispersion analysis (ANOVA) and Pearson correlation coefficients. Software Minitab (© 2010 Minitab Inc.). Results. It has been shown that concentration of phosphorus in the mycelium of fungi is about 1.5 times, and in the fruit bodies is about 7 times higher of that the plant plant tissue (soil+root interface). The concentration of manganese in the mycelium is about the same as in the bulk soil and much lower in the fraction of rhizosphere. Iodine, chromium and nickel are not accumulated, neither the mycelium of fungi nor in their fruitful bodies. Copper, zinc and cadmium are accumulated in both fruit bodies and mycelium of the studied species intensively. The concentration of cadmium in the mycelium is found to be about three times higher than in the bulk soil fraction, and about twice as high as in the fraction of rhizosphere. At such concentrations of cadmium in mycelium, the later may account from 16.2 to 32.3% of the total amount of cadmium in the upper, 0-10 cm layer of forest soils. The content of cobalt and mercury in the mycelium appeared to be somewhat higher in the bulk soil, about the same as in the rhizosphere fraction, and significantly higher than in the soil-root interface fraction. Fungi did not accumulate lead neither in the mycelium nor in their fruit bodies, whereas arsenic does not accumulated in soil-root interface and only weakly accumulated by fungal fruit bodies. Conclusions As a result of the study, it was found that the content of most of the analyzed metals and non-metals in the mycelium of ectomycorrhizal fungi of the upper (0-10 cm) soil enriched with organic matter in the forest ecosystem, except for cadmium and phosphorus, does not exceed 10% of their total amount. At the same time, the content of cadmium in the mycelium of fungi was the highest − 16.2 to 32.3%, which indicates the ability of fungi to accumulate this metal. It is suggested that the percentages of the content of the elements studied in the mycelium of upper layers of forest soil is rather underestimated than overestimated.